1979
DOI: 10.1295/polymj.11.711
|View full text |Cite
|
Sign up to set email alerts
|

Transitions and Relaxations in Poly(trifluoroethylene)

Abstract: S:Transition behavior in poly(trifluoroethylene)(P3FE) was studied (I) by mechanical-relaxation measurements, dealing with the influence of crystallinity, molecular weight, cold drawing, and copolymerization with vinylidene fluoride, and (2) by dielectric-relaxation measurement at various frequencies up to 300 kHz. In P3FE, two transitions have been observed with peaks at 50°C (designated a) and -20°C (designated /3) by mechanical-relaxation measurement at 35 Hz. It was found that the a-transition was related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Yagi observed that anomalous linkages such as head-to-head or tailto-tail are contained considerably in PTrFE. 4 These linkages possibly yield defects in crystals, and annealing may decrease the disorder or irregular conformations around this type of defects. The f3' relaxation is likely related to this type of defect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yagi observed that anomalous linkages such as head-to-head or tailto-tail are contained considerably in PTrFE. 4 These linkages possibly yield defects in crystals, and annealing may decrease the disorder or irregular conformations around this type of defects. The f3' relaxation is likely related to this type of defect.…”
Section: Resultsmentioning
confidence: 99%
“…Yagi did not find the resolved {3' relaxation so that he ascribed the f3 relaxation partly to local molecular motions around this type of defect in crystals. 4 As considered in some crystalline polymers, row vacancy defects at chain ends are also present in crystals. 5 The activation energy for the /Jc relaxation in PTrFE was similar to those for the chain end defects in crystals of polyethylene and PCTFE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the addition of over 17 mol% TrFE units via direct polymerization process, P(VDF‐ co ‐TrFE) chains prefer all ‐trans conformation and unit cell of β phase directly 17. Yagi et al18–20 have investigated the molecule conformation and crystalline form of P(VDF‐ co ‐TrFE) over the entire range of composition by means of X‐ray diffraction (XRD) and infrared spectroscopy. Pure PTrFE was found to be a stereo‐irregular containing ∼50% of inversely added monomeric units and adopt a 3/1‐helical conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Pure PTrFE was found to be a stereo‐irregular containing ∼50% of inversely added monomeric units and adopt a 3/1‐helical conformation. The addition of less than about 85 mol % VDF could result in trans or trans ‐like conformation while higher VDF concentrations would yield TGTG′ conformation in the copolymers 18–21. Mechanical stretching process, external electric‐field polarization, and thermal treatment have been reported to exhibit significant influence on the final crystalline phases of these polymers as well 22–26…”
Section: Introductionmentioning
confidence: 99%